Nafamostat mesilate attenuates renal fibrosis by suppressing the IL-17 signaling pathway - Liao, Weili; Fan, Rui; Du, Yuman; Wang, Hairong; Yang, Yong; Tian, Yuan (Frontiers in Pharmacology, 2025)
IntroductionChronic kidney disease (CKD) is a global public health concern characterized by progressive renal function decline and fibrosis, ultimately leading to end-stage renal disease (ESRD). Renal tubular injury and renal interstitial fibrosis are key contributor to this process. Granzyme B (GZMB), a serine protease, has been studied for its role in inducing apoptosis during immune defense. However, the role of GZMB in tubular injury and renal interstitial fibrosis remain unclear. Nafamostat mesylate (NM), a broad-spectrum serine protease inhibitor which is used for anticoagulation during hemodialysis in the clinic. This study aims to investigate the effects of GZMB on renal injury and renal interstitial fibrosis, and further explore the mechanisms of action NM intervention on renal injury and renal interstitial fibrosis.MethodTo elucidate the therapeutic mechanisms of NM in renal fibrosis, we integrated in vivo unilateral ischemia-reperfusion injury (UIRI) models with in vitro experiments using human proximal tubular epithelial (HK-2) cells stimulated by TGF-β or GZMB. The therapeutic effect of NM was evaluated through renal function examination, histopathological assessment, immunofluorescence staining, Western blot and qRT-PCR analysis. In addition, RNA sequencning is conducted to identify key pathways. These methods collectively reveal the mechanisms both in vivo and in vitro by NM improves renal injury and fibrosis.ResultGZMB was upregulated in various mouse models of renal fibrosis as well as in TGF-β-stimulated HK-2 cells. In vitro, GZMB treatment induced HK-2 cell injury, inflammatory responses, and partial epithelial-mesenchymal transition (p-EMT). Transcriptomic analysis demonstrated that the combined administration of GZMB and perforin significantly altered the expression of genes associated with apoptosis, inflammation, and fibrosis. The serine protease inhibitor NM attenuated GZMB-induced HK-2 cell injury, inflammatory responses, and p-EMT. Furthermore, NM suppressed TGF-β-induced p-EMT. In a murine model of UIRI, NM administration improved renal function, reduced fibrotic deposition, and exerted protective effects against apoptosis and mitochondrial dysfunction. RNA-seq analysis suggested that the renoprotective effects of NM were mediated through inhibition of the IL-17/c-Fos signaling pathway.DiscussionThis study confirmed that GZMB promotes the process of renal fibrosis by inducing renal tubular cell injury and p-EMT. NM can effectively antagonize the above-mentioned harmful effects induced by GZMB and TGF-β, and improve renal function and alleviate fibrosis in mouse models. Its renal protective effect is related to the inhibition of the IL-17/c-Fos signaling pathway. The above content proves that NM can be a potential drug for the treatment of CKD.